2020
DOI: 10.1111/iju.14293
|View full text |Cite
|
Sign up to set email alerts
|

Role of urinary cations in the etiology of interstitial cystitis: A multisite study

Abstract: Objective To determine whether patients with interstitial cystitis have elevated levels of toxic urinary cations, to identify and quantify these cationic metabolites, and to assess their cytotoxicity. Methods Isolation of cationic fraction was achieved by solid phase extraction using an Oasis MCX cartridge on urine specimens from interstitial cystitis patients and controls. C18 reverse phase high‐performance liquid chromatography was used to profile cationic metabolites, and they were quantified by the area un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…14 Parsons et al examined the effects of cations in urine and found that urine with higher levels of cations can damage the bladder's mucus and initiate an epithelial leak. 15 Furthermore, a review by Klumpp outlined another plausible theorydpelvic cross talk. 16 According to this theory, comestibles that evoke a response in the colon or surrounding organs could exacerbate the bladder- centric symptoms felt by IC/BPS patients.…”
Section: Discussionmentioning
confidence: 99%
“…14 Parsons et al examined the effects of cations in urine and found that urine with higher levels of cations can damage the bladder's mucus and initiate an epithelial leak. 15 Furthermore, a review by Klumpp outlined another plausible theorydpelvic cross talk. 16 According to this theory, comestibles that evoke a response in the colon or surrounding organs could exacerbate the bladder- centric symptoms felt by IC/BPS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pathophysiological changes resulting in altered bladder permeability represent a compelling theory for the origins of HIC. A recent multi-site study determined that patients with IC/BPS had significantly elevated levels of cationic toxins within their urine, though the study did not stratify by disease subtype [113]. Increased levels of cationic toxins can damage the bladder and increase permeability.…”
Section: Interstitial Cystitismentioning
confidence: 99%
“…Finally, although it is common knowledge that urine pH is influenced by diet and that acidic urine enhances bladder pain and frequent urination, diet modification therapy is often not vigorously enforced in IC/BPS patients [39]. Some studies have also reported that substances such as potassium and toxic cations in urine can modify lower urinary tract symptoms of IC/ BPS [40] and that various dietary factors including citrus fruits, tomatoes, spicy food, alcohol, and caffeinated beverages can trigger a flare (defined as urologic or pelvic pain that is much worse than usual) in IC/BPS patients [41]. Therefore, further research in this field of dietary modification is strongly recommended to improve the treatment of IC/BPS.…”
Section: Need For Science-based Dietary Regimensmentioning
confidence: 99%